An Investigation of Auditors’ Judgments When Companies Release Earnings Before Audit Completion - BHASKAR, LORI SHEFCHIK; HOPKINS, PATRICK E.; SCHROEDER, JOSEPH H. (Journal of Accounting Research, 2019)
ABSTRACT The majority of U.S. public companies release annual earnings prior to the completion of audit fieldwork. We investigate this phenomenon in a controlled experiment with audit partners and senior managers. We find that releasing earnings before completion of the audit pressures auditors to adopt the goals of management, thereby reducing the likelihood of post‐announcement audit‐adjustment recommendations. We also examine the effect of audit committee (AC) strength in improving auditors’ judgments after annual earnings are released. When ACs are actively involved in accounting issues and proactively communicating with auditors—characteristics currently lacking in most ACs—the negative effects on auditors’ judgments are completely mitigated. Our study provides evidence on potential unintended consequences of early release of earnings and the importance of investing in high‐quality ACs to mitigate adverse effects of client pressures on audit judgment and financial reporting quality.